Hydrogen Production Scheduling Strategy for Photovoltaic Electrolysis of Water Considering Dynamic Hydrogen Prices - LI Janlin, WANG Dalong, ZHAO Wending, XIN Dixi, ZOU Fei (Dianli jianshe)
To promote the commercial application of photovoltaic electrolysis hydrogen production technology， this study proposes a scheduling strategy for photovoltaic electrolysis hydrogen production that takes into account the dynamic hydrogen price mechanism. First， two operation modes， residual electricity grid connection and residual electricity hydrogen production， were considered. A photovoltaic electrolysis water hydrogen production system operation model was constructed， and under relevant constraints， a scheduling strategy for the photovoltaic electrolysis water hydrogen production system was proposed. The system aims to maximize overall revenue and introduces a utility function to optimize the satisfaction and sales revenue models of hydrogenation users. Second， to maximize sales revenue and user satisfaction， an optimal dynamic hydrogen price was obtained using the NSGA2. Finally， the CPLEX solver was used to obtain the optimal scheduling strategy scheme for different scenarios. The optimized operation results and their economic benefits were analyzed， and the operation results and economic benefits under different scenarios were compared. The simulation results show that the dynamic hydrogen pricing mechanism adopted in the photovoltaic electrolysis hydrogen production scheduling strategy can effectively increase hydrogen sales revenue， guide hydrogenation demand in an orderly manner， and improve the economic efficiency of photovoltaic electrolysis hydrogen production.